2021
DOI: 10.3390/plants10091933
|View full text |Cite
|
Sign up to set email alerts
|

Phytopathological Threats Associated with Quinoa (Chenopodium quinoa Willd.) Cultivation and Seed Production in an Area of Central Italy

Abstract: In 2017, in a new Chenopodium quinoa cultivation area (Central Italy), emergence failures of the Titicaca, Rio Bamba, and Real varieties, whose seeds were obtained the previous year (2016) in the same location, were observed. Moreover, leaf disease symptoms on the Regalona variety, whose seeds came from Chile, were detected. Visual and microscopic analyses showed the presence of browning/necrotic symptoms on the seeds of the three varieties whose emergence in the field had failed. In addition, their in vitro g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
1
6
0
2
Order By: Relevance
“…Moreover, even if Fusarium spp. were not detected in the EU samples analyzed in this investigation, the presence of Fusarium secondary metabolites reported by Ramos-Diaz et al [ 23 ] in quinoa seeds from Denmark showed that also Fusarium species can be associated with EU quinoa seed samples, as also previously reported by Beccari et al [ 51 ]. However, both Ramos-Diaz et al [ 23 ] and Beccari et al [ 51 ] refer to the species Fusarium equiseti , while in this study, the non-mycotoxigenic species Fusarium oxysporum was identified in four extra-EU samples.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Moreover, even if Fusarium spp. were not detected in the EU samples analyzed in this investigation, the presence of Fusarium secondary metabolites reported by Ramos-Diaz et al [ 23 ] in quinoa seeds from Denmark showed that also Fusarium species can be associated with EU quinoa seed samples, as also previously reported by Beccari et al [ 51 ]. However, both Ramos-Diaz et al [ 23 ] and Beccari et al [ 51 ] refer to the species Fusarium equiseti , while in this study, the non-mycotoxigenic species Fusarium oxysporum was identified in four extra-EU samples.…”
Section: Discussionsupporting
confidence: 87%
“…Despite the abundant literature concerning the infection of cereals by mycotoxigenic fungi and relative contamination by mycotoxins, the number of scientific papers concerning the presence of these contaminants in pseudocereals, quinoa in particular, is smaller [ 18 , 19 , 20 , 21 , 22 , 48 , 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aspects related to quinoa diseases were reviewed by Colque-Little et al [ 19 ], who summarized existing information on symptoms and causal agents. In Central Italy, the presence of P. variabilis and F. equiseti was monitored on C. quinoa [ 20 ]. Seed dormancy and breeding as well as nonbreeding strategies for enhancing resistance to preharvest sprouting in quinoa were reviewed by McGynti et al [ 21 ].…”
Section: Ecophysiological Traits and Adaptabilitymentioning
confidence: 99%
“…in Peru (Danielsen et al, 2003), damping-off (caused by F. avenaceum and Fusarium spp.) in the Czech Republic (Dřímalková & Veverka, 2004) and Japan (Isobe et al, 2019), browning or necrotic symptoms on seeds (caused by the F. incarnatum-equiseti species complex) in Italy (Beccari et al, 2021), and quinoa panicle rot (caused by F. citri) in China (Yin et al, 2022). Notably, there has been no detailed research on the species of pathogens associated with Fusarium wilt (Danielsen et al, 2003).…”
mentioning
confidence: 99%